Improving Patient Outcomes in Respiratory Therapy: The Critical Role of Nursing Interventions - SHAIKH , WIAM MOHAMMED; HINDI, NOUF JAMAAN ABDU; GHAMMARI, NADA ABDULLAH; SAK , DALAL ABDU; OQADY, WEGDAN HUSSAN TALA; SHUWAYI , TAHANI MOHAMMED ABDULLAH; YAHYA, NOUF MAKHDRI JABER; HUMEDI, HAYAM MOHAMMED ABDULLAH; KHWAJI, TURKI HADI (Journal of Ecohumanism, 2024)
Respiratory therapy plays a crucial role in managing acute and chronic respiratory conditions, yet its effectiveness is significantly influenced by nursing interventions. This article explores the critical role of nurses in improving patient outcomes in respiratory therapy through evidence-based practices, including patient assessment, oxygen therapy management, airway care, medication administration, and complication prevention. Nursing interventions enhance treatment adherence, reduce hospital readmissions, and improve overall patient well-being. Challenges such as staffing shortages, limited specialized training, and communication gaps are also discussed, along with recommendations for improving multidisciplinary collaboration and continuous professional development. The findings emphasize the necessity of integrating nursing expertise into respiratory therapy protocols to optimize patient care and treatment success.